Theoretical investigation of bridge seismic responses with pounding under near-fault vertical ground motions - Yang, H.; Yin, X.; Hao, Hong; Bi, Kaiming (Multi-Science Publishing, 2015)
Vertical earthquake loading is normally regarded not as important as its horizontal components and are not explicitly considered in many seismic design codes. However, some previous severe near-fault earthquakes reveal that the vertical ground motion component can be much larger than the horizontal components and may cause serious damage to the bridge structures. This paper theoretically investigates the vertical pounding responses of a two-span continuous bridge subjected to the severe near-fault vertical ground motions. The bridge is simplified as a continuous beam-spring-rod model. The structural wave effect and the vertical pounding between the bridge girder and the supporting bearing are considered, and the theoretical solutions of bridge seismic responses are derived from the expansion of transient wave functions as a series of eigenfunctions. The effects of vertical earthquake and vertical pounding on the bridge bearing, girder and pier are investigated. The numerical results show that the severe vertical earthquake loading may cause the bridge girder to separate from the supporting bearing and hence result in vertical poundings between them when they are in contact again. These vertical poundings can significantly alter the seismic responses of the bridge structure and may cause severe damage to the bridge components such as bridge girder, supporting bearing and bridge pier. Neglecting the influence of vertical earthquake loading may lead to inaccurate estimation of seismic responses of bridge structures, especially when they are subjected to near-fault earthquake with relatively large vertical motion.